Investigation on environmental care towards sustatainable solid waste management using exploratary factor analysis at UiTM Tapah Campus - Faridah, Zulkipli; Nurul Husna, Jamian; Ilya Zulaikha, Zulkifli; Zulkifli Mohd, Nopiah (Universiti Teknologi MARA, Perak, 2018)
The objective of this research is to study the environmental care among UiTM Tapah Campus towards sustainable solid waste management. A set of questionnaire comprised of two parts, which are background of respondent and environmental care components and were distributed among 185 students. The statistical technique exploratory factor analysis (EFA) was implemented to classify the components. As a result, the research revealed that there are five main components which are knowledge, practice, attitude, perception and awareness can be classified by 21 questions. The result led to formulate a new set of questionnaire. This new set of questionnaire will be distributed for further research which to investigate the level of environmental care among the UiTM Tapah Campus student.